Learners with Disabilities and COVID-19 School Closures : Findings from a Global Survey Conducted by the World Bank’s Inclusive Education Initiative - World Bank (World Bank, Washington, DC, 2021)
At the onset of the coronavirus disease (COVID-19) pandemic, the world quickly experienced a crisis within a crisis, a global public health emergency that exacerbated educational inequalities within a ‘learning crisis’ that was already occurring for hundreds of millions of young people who were attending school without acquiring basic skills in literacy and numeracy (World Bank 2019). Specifically, COVID-19 intensified this learning crisis through two global shocks to education: massive school closures and a subsequent economic recession (World Bank 2020b). In the spring of 2020, at the peak of the pandemic, 180 countries experienced temporary school closures, affecting 1.5 billion young people or 94 percent of the student population worldwide (World Bank, n.d.). For more than half of these students, schools would remain closed for more than seven months. A year after the worldwide spread of COVID-19, in March 2021, schools remained closed in more than 50 countries (World Bank, n.d.). Governments tried to respond to these unprecedented times by employing remote learning initiatives using both digital and nondigital formats. However, inadequate infrastructure or the absence of trained teachers who could quickly transition to online models of teaching often limited the effectiveness of such responses. This study arose from a deep need to understand the experiences of learners with disabilities during the onset of COVID-19 and the accompanying school closures. The survey was disseminated in May 2020 to inform the ‘just in time’ issues paper, Pivoting to Inclusion: leveraging Lessons from the COVID-19 Crisis for Learners with Disabilities (World Bank 2020a) (referred henceforth as Pivoting to Inclusion). The Pivoting to Inclusion report highlighted important recommendations for policy makers and practitioners to provide an inclusive and quality education for learners with disabilities during school closures and future emergencies, including the use of Universal Design by Learning (UDL) and a twin-track approach to inclusive education sector planning. A twin-track approach involves two basic principles: (1) ensuring that mainstream education programs are designed for all learners; and (2) developing targeted support to address the specific needs of children with disabilities (World Bank 2020a). The findings from this survey show various examples of f these two tracks, as well as the importance of UDL in remote teaching and learning for learners with disabilities.